The Influence of Psychological Safety on Students’ Creativity in Project-Based Learning: The Mediating Role of Psychological Empowerment - Han, Shenghao; Liu, Dewen; Lv, Yiliang (Frontiers in Psychology, 2022)
Creative-oriented new educational model will shape the direction and appearance of world development. This study focuses on the role of psychological safety and psychological empowerment in improving students' creativity in the context of project-based learning from the perspective of student empowerment. Based on the theory of self-determination, we propose that psychological safety positively affects students' creativity through psychological empowerment, and fault-tolerant culture plays a positive role in it. In this study, 238 students who participated in project-based learning were randomly selected to conduct a questionnaire survey. The results show that there is a positive correlation between psychological safety and creativity, and psychological authorization plays an intermediary role in the relationship between them. The fault-tolerant culture enhances the direct influence of psychological safety on psychological authorization and the indirect influence of psychological safety on creativity. Theoretical and practical implications were also discussed.